The Role of COVID-19 and CSR Disclosure in Weakening Corporate Value - Adinda Nurul Auliya; Reschiwati, Aang Syahdina (Adisam Publisher, 2025)
This study aims to analyze Profitability (ROE), Company Size (SIZE) and Dividend Policy (DPR) on Company Value (PER), the role of Covid-19 (C-19) and CSR Disclosure (CSR) in weakening and strengthening Profitability (ROE), Company Size (SIZE) and Dividend Policy (DPR) on Company Value (PER). The population of this study is consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the period 2014-2023. The sample of this study using the purposive sampling method obtained 11 consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the period 2014-2023, resulting in a total of 110 observation data. The data analysis method uses Eviews12. The findings of the study indicate that ROE has a negative impact, while SIZE and DPR have no effect on PER. C-19 strengthens the relationship between ROE and PER, but does not moderate the effect of SIZE and DPR on PER. CSR actually weakens the relationship between ROE and PER and does not moderate the effect of SIZE and DPR on PER. The novelty of this research is that it uses a 10-year period to examine company value.